ANALISIS GAYA BAHASA DAN NILAI PENDIDIKAN DALAM SERAT WEDHATAMA PUPUH PANGKUR SEBAGAI BAHAN AJAR MATA PELAJARAN BAHASA JAWA TINGKAT SMA (SUATU KAJIAN STILISTIKA) - Bahtiar, Muhammad Yusuf; Waluyo, Budi; Saddhono, Kundharu (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2017)
This research do in order to identify and describe: (1) language style in Serat Wedhatama pupuh Pangkur; (2) the moral value in Serat Wedhatama pupuh Pangkur; (3) relevance of language style and moral value in Serat Wedhatama pupuh Pangkur with learning Javanesse language subjects in Senior High School.The form of this research is descriptive qualitative using analysis documents method. Source of the data in this research include document, that is Serat Wedhatama pupuh Pangkur created by Kanjeng Gusti Pangeran Adipati Arya (KGPAA) Mangkunegara IV and informant who is an expert in language style and Java’s serat. Data collection technique used is the technique of library research also interviews with sources related to the validity of the test by using triangulation of data sources. Data analysis technique in this research is an interactive model that consists of four components, that is: (1) data collection; (2) data reduction; (3) data presentation; and (4) conclusion. Based on the results of this research the writer can conclude that the style of language used in form of Serat Wedhatama pupuh Pangkur are: (1) the word style that used by the author is connotative word, concrete, interjection, uptake word, also proper name and distinctive greeting; (2) sentence style that used is sentence with investigation the structure  and means of rhetoric; (3) sound style that used by the author is purwakanthi swara (assonance), sastra (alliteration), and basa or lumaksita; (4) the illustration that used is visual imagery, audio, touching, and movement; and (5) figure of speech that used are simile and metonymy. In addition, the moral value of the Serat Wedhatama pupuh Pangkur are: (1) religious value; (2) sociality value; (3) morality value; and (4) cultural value. Analysis of the language style and moral value in this Serat Wedhatama pupuh Pangkur is relevant to the materials of the Javanesse language subjects because of that Serat Wedhatama pupuh Pangkur contains some elements of aesthetic and noble values that can be used as teaching materials of  the Javanesse language subjects.